Challenges in the use and understanding of English technical jargon among Malay architecture undergraduates in Malaysia / Abdul Rahman Khamaruzaman, Maisarah Ahmad Kamil and Iznny Ismail - Khamaruzaman, Abdul Rahman; Ahmad Kamil, Maisarah; Ismail, Iznny (Universiti Teknologi MARA, 2022)
The ability to use and especially understand technical language is crucial to increase one’s understanding and command over any field of study, especially in the current era where graduates are expected to become adept not only in technical skills, but also in communication skills to adjust to rapid changes in the industry. Howev-er, few studies have been conducted on the challenges faced especially by architecture students in understand-ing English technical jargon in their field, even though past research has highlighted this issue in the local con-text before. Hence, a quantitative study was conducted to explore the level of understanding, use and challenges faced by tertiary architectural students pertaining to architectural jargon in their studies. A questionnaire adapted from sources of past literature was used to answer the research questions. Data was collected from 117 Malay architectural students in Malaysia and analysed to produce descriptive findings of the results. Interest-ingly, the results showed that the students tended to understand technical jargon, however, the challenges they faced were in knowing how to use the terms correctly, which points to issues not in receptivity, but in produc-tion. Giving examples, explaining the correct ways to use the terms and providing opportunities for them to continuously use the terms were among the suggestions that the students gave to further improve the teaching of technical classes in university. Thus, the findings provide a good basis for universities and lecturers especial-ly to further improve the language ability, especially in technical jargon usage, among Malay undergraduate architecture students in Malaysia.